Penerapan PSAK No.109 Tentang Pelaporan Keuangan Akuntansi Zakat/Infaq/Sedekah Pada Badan Amil Zakat Kabupaten Karawang Tahun 2021 - Gina Sonia; Wirman Wirman (Peneliti.net, 2023)
The zakat collection agency functions to collect, distribute and use zakat, infaq/alms, manage it in a professional, open and in accordance with financial resporting standards because these funds will be accounted for. The standard used by PSAK 109 explains the Accounting for Zakat, Infak, and Alms, the aim is to find responses regarding all the provisions of PSAK 109. This study aims to determine the process of financial reporting for Baznas, Karawang city in applying PSAK 109. This method uses a quantitative method. Secondary data is document. The document contains a government regulation law and financial reports for 2021. Baznas Karawang Regency has adopted Accounting Standard Regulation 109 regarding Financial Reporting Accounting for Zakat, Infak/alms. then they must comply with these standards in reporting financial and accounting zakat, infaq, or alms they receive.